Descriptive Study of Some Osteological Parts of Rosy Stone Lapper (Garra rossica) from Mashkid Basin of Iran - Zamani-Faradonbe, Mazaher; Keivany, Yazdan (International Journal of Zoology, 2021)
Since osteological structures of fishes provide important biological and ecological information, studying these structures is valuable. On the other hand, due to lack of data on the osteology of stone lappers, the present study was conducted to provide detailed descriptive osteology of Garra rossica from Mashkid basin, southeastern Iran, comparing it with those of G. typhlops from the Bagh-e Loveh cave, Iran, G. rossica from Nahang River, Mashkid Basin, and G. persica from Zahak River, Sistan basin. For this purpose, 15 specimens of G. rossica were captured from Ladiz River, Mashkid Basin, using an electrofishing device, and fixed in 10% buffered formalin. Then, the specimens were cleared and stained with alcian blue and alizarin red for osteological investigations. A detailed description of the osteological features of G. rossica was provided. Based on the results, several differences were observed between the four species. G. rossica can be distinguished from G. typhlops, G. persica, and G. rossica based on the shape of suspensorium and opercular series, pharyngobranchial bones, ventral and pectoral girdles, caudal, dorsal, and anal fins skeleton, and shape and number of infraorbital elements.